Pasireotide-induced hyperglycemia in Cushing’s disease and Acromegaly: A clinical perspective and algorithms proposal - Witek, Przemysław; Bolanowski, Marek; Krętowski, Adam; Głowińska, Aleksandra (Frontiers in Endocrinology, 2024)
Pasireotide is an effective treatment for both Cushing's disease (CD) and acromegaly due to its ability to suppress adrenocorticotropic hormone and growth hormone, and to normalize insulin-like growth factor-1 levels, resulting in tumor shrinkage. However, it may also cause hyperglycemia as a side effect in some patients. The aim of this study was to review previous recommendations regarding the management of pasireotide-induced hyperglycemia in patients with CD and acromegaly and to propose efficient monitoring and treatment algorithms based on recent evidence and current guidelines for type 2 diabetes treatment. In about 25% of patients with CD and 50% of patients with acromegaly, pasireotide-induced hyperglycemia does not require drug therapy or can be managed with diet and oral antidiabetic agents. The risk of pasireotide-induced hyperglycemia is higher in patients with diabetes or prediabetes at baseline. Moreover, pasireotide used in the treatment of CD may lead to more frequent and difficult-to-treat glycemic disorders than those observed in acromegaly. Based on the pathomechanism of hyperglycemia, we suggest using metformin as the first-line therapy, followed by glucagon-like peptide-1 and/or sodium-glucose co-transporter-2 inhibitor, and finally insulin in patients with pasireotide-induced hyperglycemia. We propose algorithms for the management of glucose metabolic disorders caused by pasireotide treatment in patients with CD and acromegaly, including those with chronic kidney disease and at high cardiovascular risk.